Personalized Writing Tasks to Enhance Students' Speaking Proficiency - Simatupang, Catharine; Magdalena, Dameria (English Education: Jurnal Tadris Bahasa Inggris, 2025)
This study investigates the impact of personalized writing tasks on the speaking proficiency of 11th-grade students, focusing on fluency, coherence, and vocabulary. An explanatory sequential mixed-methods design was utilized. Quantitative data were gathered from pre-tests and post-tests involving an experimental group (N=35) and a control group (N=35), while qualitative data were collected through questionnaires and semi-structured interviews to explore student perceptions. Quantitative analysis showed that the experimental class achieved a significantly higher mean improvement (10.17 points) compared to the control group (6.51 points). Qualitative findings indicated that 91% of students felt more fluent and 86% felt more confident when speaking about self-selected topics. Personalized writing tasks effectively bridge the gap between reflective writing and spontaneous speaking, providing a meaningful strategy for secondary school English education.